Proceso de atención de enfermería en neonato con diagnóstico de sífilis congénita. - Gavilánez Correa, Jahir Jamlec (2024)
This clinical case study at the HANM emphasizes the application of the nursing care process in a 7-day-old female patient diagnosed with congenital syphilis, a disease that occurs when an infected mother transmits the Treponema pallidum bacterium to the baby during pregnancy or childbirth. This is a descriptive, cross-sectional study whose objective is to provide nursing care to restore the patient's health condition. The objective of this case study is to establish a care plan applying the Nursing Care Process (PAE) in the patient through the description of the clinical history, health status, applied tests and identification of altered functional patterns. Marjory Gordon's assessment by functional patterns is an invaluable tool that allows the nursing staff to have a more complete vision of the person in their physical, emotional, social and cognitive spheres, which allows determining the degree of affectation in their current state of health. Once the assessment proposed by this theorist and in relation to the clinic, the alteration of the following patterns was evidenced: perception - health management and metabolic nutritional. Finally, the nursing care process enabled the patient's satisfactory recovery during her 14-day hospitalization through various interventions. Basic physiological care was applied with the purpose of addressing skin deterioration and ineffective thermoregulation. In addition, these interventions contributed to the eventual improvement of the patient's skin and her ability to maintain a normal body temperature, thus facilitating her physiological stability. The process also favored the patient's rest and promoted adequate breast milk feeding, leading to optimal recovery. In summary, our work as nurses was successfully accomplished, achieving each of the objectives established in this case study.